FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT MUSLIM TERHADAP PRODUK BAITUL MALL WA TAMWIL (BMT) SIDOGIRI CABANG PEMBANTU TELUK BATANG DAN CREDIT UNION (CU) KHATULISTIWA BAKTI KP TELUK BATANG - Ema Elisa (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study analyzes the factors that influence Muslim community interest in the products of Baitul Mall Wa Tamwil (BMT) Sidogiri Branch of Batang Batang And Credit Union (CU) equatorial community service at the Batang Bay KP. This research uses descriptive methods in a quantitative approach. The population of this study was 38 respondents based on the specified characteristics. The sample also 38 people, the technique used to collect data is a questionnaire, while to analyze the data researchers use regression analysis to find answers to the factors that affect the interests of customers and members of the products offered that affect it namely the attractiveness of advertising / promotion, sales force / employee competency and customer value. The data analysis tool is multiple linear regression in the SPSS version 22.0 program. The results of the data analysis are done, the researcher concludes the factors that affect the interest of the Customer / BMT and CU members of the products offered, the results of the data analysis show that the research model has a corresponding well and all research hypotheses can be proven. The conclusion drawn is the attractiveness of advertising / promotion, sales force / employee competence and customer value significantly influence interest. Keywords: Interest of Muslim Communities, BMT Sidogiri, Credit Union (CU) equatorial service at Teluk Batang KP.